2014
DOI: 10.7783/kjmcs.2014.22.6.463
|View full text |Cite
|
Sign up to set email alerts
|

Soil Physico-Chemistry and Saponins Content of Platycodon grandiflorum Radix Cultured from Different Sites in Gyeongnam Province

Abstract: : This study was carried out in order to survey the soil physico-chemical, morphology and content of saponins of 5 year-old Platycodon grandiflorum radix from different areas in Gyeongnam. Soil physical properties was showed 1.01-1.29 of bulk density of soil and soil hardness was increased with increasing soil depth, especially below the 30 ㎝, however it was maintained or small increased below the 40 ㎝. T-N and OM contents of top soil were highest at Geochang as 0.27% and 56.9 g/kg, respectively, compared to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Previous studies reported that platycodin D or polygalacin D were the most dominant saponin derivative, and the contents of each compound indicated values as diverse as 246.2 ~ 1196.9 (mg/100 g, DW) and 191.6 ~ 1241.0 (mg/100 g, DW) when changing soil conditions, dividing the root, and changing the cultivated region [ 31 , 48 , 49 , 50 , 51 , 52 , 53 ]. However, Lu et al showed that for the individual saponin content of various cultivated regions, some provinces revealed platycoside E (69.1 ~ 346.2 mg/100 g, DW) to be the most prevalent compound; however, other regions showed platycodin D (40.9 ~ 511.3 mg/100 g, DW) to be the predominant compound [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that platycodin D or polygalacin D were the most dominant saponin derivative, and the contents of each compound indicated values as diverse as 246.2 ~ 1196.9 (mg/100 g, DW) and 191.6 ~ 1241.0 (mg/100 g, DW) when changing soil conditions, dividing the root, and changing the cultivated region [ 31 , 48 , 49 , 50 , 51 , 52 , 53 ]. However, Lu et al showed that for the individual saponin content of various cultivated regions, some provinces revealed platycoside E (69.1 ~ 346.2 mg/100 g, DW) to be the most prevalent compound; however, other regions showed platycodin D (40.9 ~ 511.3 mg/100 g, DW) to be the predominant compound [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Herbs collected from different regions will show certain differences both in chemical constituents and in pharmacological activities [ 17 ]. For example, saponins in the root of PG from different sites in Gyeongnam Province, Korea showed different contents [ 18 ]. The 1 H-NMR-based metabolomics with OPLS-DA statistical models was used to cluster the ginseng samples from Korea and China, and the result suggested that the chemical profiles from two countries are quite different due to their different geographical origins [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Twenty metabolites were characterized from the root of PG, which is purchased from a Daegu Herbal Market in Daegu Gyeongbuk Province, Korea. As is well known, herbs collected from different production region will show certain differences both in chemical constituents and pharmacological activities . Hence, PG produced in Jilin Province, China was taken as samples in this paper.…”
Section: Introductionmentioning
confidence: 99%